PROFIL ORGANISASI PEMUDA BATAK BERSATU (PBB) DI KOTA PEKANBARU - Fitra Meliadona; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Pemuda Batak Bersatu is a social organization. The purpose of this organization is to strengthen the bonds of brotherhood among the Batak people regardless of religion, and to build a sense of solidarity, tolerance and mutual cooperation. The purpose of this research: 1). To find out the management profile of the United Batak Youth Organization in Pekanbaru City. 2). To find out how the role of the United Batak Youth organization towards the community in Pekanbaru City. This research uses a qualitative method with a descriptive study. In this case the determination of information using purposive sampling technique. Retrieval of research data is done by interviews, observation, and documentation. The Pemuda Batak Bersatu Organization is an association of Batak people whose activities are socially based. Its role in the community is from a social perspective, namely voluntarily escorting, protecting and assisting both in grieving, marriage or religious activities, as well as serving people who need assistance the Pemuda Batak Bersatu. From an economic perspective, by distributing groceries to the community and helping to provide jobs for those in need. Keywords: Profile, Pemuda Batak Bersatu, Organization